Implementation of a Geographic Information System in Website Design to Visualize Routes and Distances - Yudhistira Pradana; Tri Listyorini; Endang Supriyati (CV. Media Digital Publikasi Indonesia, 2026)
This journal research was conducted with the primary objective of developing a system capable of visualizing the route and distance from SMK Raden Umar Said Kudus to various boarding houses located within Kudus Regency. The increasing number of students enrolling in the school, including those from outside the region, has created a growing need for accessible information regarding temporary accommodation near the school. Therefore, the proposed system is designed to assist students in identifying suitable boarding houses by providing geographic visualization of their locations and distances from the school. To achieve this objective, the system utilizes the Leaflet library as the main mapping tool to visualize geographic information in an interactive web based environment. Leaflet enables the display of maps, routes, and distance calculations in a user friendly format, making it easier for users to understand spatial relationships between the school and nearby boarding houses. The system itself is developed using PHP as the primary programming language. In addition, JavaScript is integrated with the Leaflet library to handle map interactions and geographic data visualization. The Waterfall development model was chosen as the system development methodology due to its clear and sequential. Through this approach, the research aims to produce a functional Geographic Information System that helps students efficiently locate temporary housing during their study period at SMK Raden Umar Said Kudus while also providing useful information for boarding house owners.